Mobile banking apps curation: Assessing the factors that influence mobile banking’s continuous use amongst Millennials and Generation Z - Mashishi, Neo (University of the Witwatersrand, Johannesburg, 2024)
The proliferation of mobile banking platforms and the widespread use of intelligent devices like smartphones and tablets have caused a paradigm change in the banking industry in recent times. Millennials and Generation Z (Gen Z), dubbed the "digital natives," make up most of these service consumers. Millennials and Gen Z are increasingly using mobile banking apps, which has transformed how financial services are delivered. Nevertheless, despite being widely adopted, banks need help to ensure the continuous use of these apps to sustain a devoted and loyal consumer base while competing in the market. This study, therefore, investigates the factors influencing Millennials and Gen Z's continuous use of mobile banking applications. Five theoretical frameworks have been adopted to direct the research inquiry: Computers As A Social Actor (CASA), Expectation Confirmation Theory (ECT-IS), Social Response Theory (SRT), Task Technology Fit (TTF), and the Unified Theory of Acceptance and Use of Technology (UTAUT). The study adopted these frameworks based on their theoretical and empirical applicability and ability to provide perspectives into the variables impacting Millennials and Gen Z's continuous use of mobile banking apps. The study employed SPSS (Statistical Package for the Social Sciences) for the analysis of descriptive statistics. To validate the theoretical model and investigate the interactions between variables, Partial Least Squares Structural Equation Modelling (PLS-SEM). PLS-SEM, Smart PLS software was used to assess the validity and reliability of the constructs as well as the strength and importance of the proposed paths in the structural model was made possible by the PLS-SEM methodology. This provided an overview of the dataset and made it possible to do a thorough analysis by outlining important features like means, frequencies, and standard deviations. The research used quota sampling for a sample size of 505 participants. The study's conclusions indicate that there is a substantial correlation among perceived anthropomorphism, expectation confirmation, service quality of mobile applications, mobile banking app satisfaction, technology fit, and consistent usage of mobile banking apps. The study’s goal is to advance our understanding of the field of banking and financial services marketing. The banking sector can apply the findings and insights to differentiate its offerings from its competitors and gain a competitive edge while potentially boosting profitability.
A research report submitted in fulfillment of the requirements for the Master of Commerce, In the Faculty of Faculty of Commerce, Law and Management, School of Business Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Anthropomorphism; Artificial Intelligence; Retail Banking; Gamification; Gen Z; Millennials; Mobile banking app continuous use; SDG-8: Decent work and economic growth; SDG-9: Industry, innovation and infrastructure